Development And Validation Of HPTLC Method For Estimation Of Rosuvastatin Calcium In Bulk And Pharmaceutical Dosage Forms - S.UMA DEVI,; E.PUSHPA LATHA,; C.V.NAGENDRA KUMAR GUPTHA,; MR.P. RAMALINGAM, (International Journal of Pharma and Bio Sciences, 2011)
A simple, specific, accurate and precise high performance thin layer chromatography (HPTLC) method has been developed for determination of Rosuvastatin Calcium (RC) in bulk and pharmaceutical dosage forms. The method uses aluminium plates coated with silica gel 60 F254 as stationary phase and Ethyl Acetate : Toluene : Methanol (6 : 2 : 2, v/v/v) as mobile phase. Densitometric evaluation of the separated bands was performed at 254 nm using Camag TLC Scanner-3 with win CAT 1.4.4 software. The RF value of Rosuvastatin Calcium (RC) was 0.32 ± 0.05. The validated calibration range was 500-2500 ng per spot (r2 = 0.9996). Results of analysis were validated statistically and by recovery studies. The method was validated according to the ICH guidelines with respect to linearity, accuracy, precision and robustness. Thus the proposed method can be used successfully for routine analysis of Rosuvastatin Calcium (RC) from tablet formulations.